HLA-Cw6 and other HLA-C alleles, as well as MICB-DT, DDX58, and TYK2 genetic variants associate with optimal response to anti-IL-17A treatment in patients with psoriasis. (1st February 2021) - Morelli, Martina; Galluzzo, Marco; Madonna, Stefania; Scarponi, Claudia; Scaglione, Giovanni Luca; Galluccio, Tiziana; Andreani, Marco; Pallotta, Sabatino; Girolomoni, Giampiero; Bianchi, Luca; Talamonti, Marina; Albanesi, Cristina
ABSTRACT: Objective : Our pharmacogenomic study evaluated the influence of the presence/absence of genetic variants of psoriasis-risk loci on the clinical response to secukinumab. Differences in the single-nucleotide polymorphism (SNP) pattern characterizing HLA-Cw6 + or HLA-Cw6 − patient subpopulations, showing high or low responses to secukinumab, were also analyzed. Methods : 417 SNPs were analyzed by Next-Generation Sequencing technology, in a cohort of 62 psoriatic patients and undergone secukinumab treatment. Univariate regression analysis was employed to examine the association between SNP and clinical response to secukinumab. Multivariate analysis was also performed to assess multivariate differences in SNP pattern of HLA-Cw6 + or HLA-Cw6 − patients showing high or low responses to secukinumab. Results : Eight SNPs in HLA-C and upstream region (rs13207315, rs6900444, rs12189871, rs12191877, rs4406273, and rs10484554), including HLA-Cw6 classical allele (rs1131118), and three in MICB-DT (rs9267325), DDX58 (rs34085293) and TYK2 (rs2304255) genes, associating with excellent response to secukinumab were identified. Importantly, rs34085293 or r s2304255 SNP status defined a subgroup of super-responder patients. We also found that HLA-Cw6 + and HLA-Cw6 − patients carried out specific patterns of SNPs associating with different responses to secukinumab. Conclusion : Assessment of HLA-Cw6, together with other allelic variants of genes, could be helpful to define patients which better benefit from anti-IL-17 therapy. Abbreviations: PASI: Psoriasis Area and Severity Index; SNP: Single-Nucleotide Polymorphism Rs: Reference SNP; PASI75: 75% reduction in Psoriasis Area and Severity Index; PASI90: 90% reduction in Psoriasis Area and Severity Index; PASI100: 100% reduction in Psoriasis Area and Severity Index; NGS: Next-Generation Sequencing; OR: Odds Ratio; CAP: Canonical Analysis of Principal coordinates; BMI: Body Mass Index; LD: Linkage Disequilibrium